Linear and nonlinear optical properties of a single dopant in GaN conical quantum dot with spherical cap. Issue 19 (1st October 2020) - El Aouami, A.; Bikerouin, M.; Feddi, K.; Aghoutane, N.; El-Yadri, M.; Feddi, E.; Dujardin, F.; Radu, A.; Restrepo, R. L.; Vinasco, J. A.; Morales, A. L.; Duque, C. A.; et al.
ABSTRACT: The states of a single dopant centre in zinc-blende GaN-based conical quantum dots with spherical cap are theoretically investigated by analytically solving the corresponding effective mass equation taking advantage of the localisation of the ionised impurity at the cone apex. Nonlinear optical response is analysed through the calculation of the coefficients of optical absorption, relative refractive index change, and second and third harmonic generation, for the chosen set of allowed electron-donor states. The behaviour of the calculated optical quantities under changes in the geometry of the system due to variations in apical width and quantum dot radius is analysed and discussed.